The Electrodeposition rhenium-tellurium alloys from chlorides asides electrolytes. - Salakhova, Elza; Tagiyev, D. B.; Kalantarova, P. E.; Asgarova, A. M. (JOURNAL OF ADVANCES IN CHEMISTRY, 2018)
There has been investigated the joint electrodeposition of rhenium with tellur from chlorides electrolyte, by measuring the cycling volt-ampere curves there has been determined the field of potentials, at the presence of which the joint electrodeposition of rhenium with sulphur takes place. It has been shown, that the joint deposition of rhenium with tellur goes with a certain depolarization, besides, the depolarization is caused by the energy emanating along formation of ReTe2 compounds. There was studied the influence of current density, temperature and acidity on the composition and quality of cathode sediments. It was established, that with the rise of current density and the temperature of electrolyte the concentration of rhenium in the alloy increases.